Politics of refusal and crip willfulness in Y-Dang Troeung’s Landbridge [Life in Fragments] and Madeleine Thien’s Dogs at the perimeter - Llarena Ascanio, María Jesús (International Journal of English Studies, 2025)
Troeung’s creative and theoretical intervention in Landbridge [A life in fragments] (2023) and Madeleine Thien’s in Dogs at the perimeter (2011) pose questions around alternative epistemologies to Eurocentric notions of healing and trauma recovery in the aftermath of mass violence. Thien’s engagement with bioscientific discourse exposes the “limits of a scientific epistemological framework for understanding the traumas induced in socially, and historically, situated contexts” (Troeung, 2013, p. 72). Both works assemble an archive that enacts a politics of refusal, or crip willfulness –“a refusal to act in accordance with the system of compulsory able-bodiedness” (Johnson & McRuer, 2014, p. 136). This act of creative resilience in the afterlife of the Cambodian Genocide is what seems to inspire Troeung and Thien, whose works acknowledge a new cripistemology (McRuer, 2018; Puar, 2017) and are foundational in their attempt at decolonizing disability in trauma narratives.